(Not to be Issued) Metternich - Coudray, H. du, 1906-1971 (London Thirty Bedford Square, 1935)
The complex personality of the Australian Chancellor is brought to light in this careful study of his life and achievements as a statesman.
Include Bibliography, Notes, Pictures and Index
Keywords: Europe -- Politics and Government